2005
DOI: 10.1111/j.1398-9995.2005.00703.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of loteprednol etabonate nasal spray suspension on seasonal allergic rhinitis assessed by allergen challenge in an environmental exposure unit

Abstract: Loteprednol 400 microg once daily is superior to placebo and the only effective dose tested in improving nasal symptoms and objective parameters in patients with SAR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Recent studies conducted in the exposure chambers in Austria [16] and Germany [17] have also mainly used TNSS to evaluate patient symptoms before and after treatment with antihistamines. Our TSS and TNSS levels were lower than those in reports on the efficacy of antihistamines for allergic rhinitis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies conducted in the exposure chambers in Austria [16] and Germany [17] have also mainly used TNSS to evaluate patient symptoms before and after treatment with antihistamines. Our TSS and TNSS levels were lower than those in reports on the efficacy of antihistamines for allergic rhinitis.…”
Section: Discussionmentioning
confidence: 99%
“…15) [187,188]. A large (n ¼ 165) environmental exposure unit (EEU) study in patients with seasonal allergic rhinitis (SAR) also confirmed that LE 400 mg once daily is effective and superior to placebo: after 14 days of treatment, patient in this LE group had significantly lower total nasal symptom scores (TNSS) than those receiving placebo (p ¼ 0.007) [189]. Cortienic Acid-Based Soft Steroids: Second Generation (Etiprednol Dicloacetate and Analogs) More recently, a new, second generation of soft steroids with a unique 17a-dichloroester substituent has been identified (44, Fig.…”
Section: Softmentioning
confidence: 99%
“…In most research on nasal drug absorption so far, liquid formulations such as solution, emulsion, and suspension have been used [912]. As compared to liquid formulations, there are many advantages of the powder formulation, such as the better stability of the solid drug, application of larger dose, and the higher concentration of the drug in the nasal mucosa [13–16].…”
Section: Introductionmentioning
confidence: 99%